2019
DOI: 10.1016/j.ppees.2019.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic relationships in two African Cedreloideae tree genera (Meliaceae) reveal multiple rain/dry forest transitions

Abstract: Resolving phylogenetic relationships allows the investigation of how species diversity has evolved in various ecosystems. The genera Entandrophragma and Khaya consist of tree species distributed in different African biomes (lowland rain forest, dry forest and savanna, montane forest), and are suitable to examine how (single or multiple events) and when the processes of diversification led to biome transitions. Based on the sequencing of plastome (pDNA: c. 160,000 bp), ribosomal DNA (rDNA: c. 5,300 bp), and hab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 60 publications
0
18
1
Order By: Relevance
“…Notes. A molecular study (Monthe et al, 2019) showed five clades in the genus, and these are mapped here (Fig. 8).…”
Section: Entandrophragma Cdcmentioning
confidence: 98%
See 3 more Smart Citations
“…Notes. A molecular study (Monthe et al, 2019) showed five clades in the genus, and these are mapped here (Fig. 8).…”
Section: Entandrophragma Cdcmentioning
confidence: 98%
“…14A). A molecular phylogeny (Monthe et al, 2019) arranged the species in two main clades, and these display a high level of allopatry ( Fig. 14A).…”
Section: Pseudocedrela Harmsmentioning
confidence: 99%
See 2 more Smart Citations
“…Morley, ), and dry climate is an important phylogenetic constraint to plant evolution for many lineages (Cássia‐Silva, Freitas, Alves, Bacon, & Collevatti, ; Olmstead, ; Qian, Jin, & Ricklefs, ). However, transitions from evergreen rain forest to seasonally dry biomes, especially savanna, are known from plant lineages in the Neotropics (Bacon, Moraes R., Jaramillo, & Antonelli, ; Lohmann, Bell, Calió, & Winkworth, ), Africa (Estrella, Forest, Wieringa, Fougère‐Danezan, & Bruneau, ; Monthe et al, ; Veranso‐Libalah, Kadereit, Stone, & Couvreur, ), and Australia (Crisp et al, ) and the floristic study of Dexter et al () suggests permeability of lowland tropical biomes globally.…”
Section: Introductionmentioning
confidence: 99%